Could Mussel Populations Be Differentially Threatened by the Presence of Microplastics and Related Chemicals? - Filipe Borges; Rosa Freitas; Ana L. Patrício Silva; Dulce Lucy Soliz Rojas; Gema Paniagua González; Montserrat Solé (Toxics)
Mussels serve as indicators of anthropogenic chemical pollution; however, the effects of microplastics and plastic-related chemicals on their health performance remain an emerging issue. In this study, mussels were exposed to a polyamide (PA; 5 μg/L) and tricresyl phosphate (TCP; 1 μg/L) for 28 days. The exposures to the two contaminants were performed independently or in combination and lasted 28 days. The results showed that the independent exposure altered enzyme activities more significantly than the combined one. Exposure to the PA significantly (p < 0.05) inhibited the antioxidant enzyme catalase (CAT) by 43.5% and the neurotransmitter enzyme acetylcholinesterase (AChE) by 40.6%, while TCP specifically inhibited carboxylesterase (CE) activity by 38.5%, all in respect to the solvent control. When both pollutants were combined, most biomarker responses were similar to control levels. To further investigate if the mussels’ response to contaminants (here, chemical compounds only) could be population-specific, a comparative study between Atlantic and Mediterranean mussels was included. Firstly, baseline detoxification defenses were contrasted in the digestive glands of each mussel population, followed by an assessment of in vitro responses to a wide range of plastic additives. The results revealed that Mediterranean mussels expressed higher baseline activities for most detoxification enzymes, although the in vitro sensitivity to the targeted chemicals was similar in both populations. Of all the plastic additives tested, TCP significantly inhibited CE activity both in vivo and in vitro. The in vitro screening also indicated that other plastic additives could act as strong inhibitors of CE. However, additional in vivo exposures in mussels are needed to confirm CE suitability as a biomarker of these chemical exposures. All together, these results also suggest critical population-level differences in susceptibility to microplastic pollution, highlighting a need for targeted conservation efforts.